Merchandising cases from the 7th International European Association for Education and Research in Commercial Distribution Conference. (Retail insights, 2003)
This issue of Retail Insights is devoted to casesfrom the 7th International EuropeanAssociation for Education and Research inCommercial Distribution (EAERCD)conference which was hosted by theUniversity of Gloucestershire Business Schoolin Cheltenham, England in July 2002 (Website - http://online.